The Imagination of Sexuality in Society and Culture: An Inquiry into the Erotic Literature of Ming and Qing Society and Gender (1600-1800) - Hsieh, Ying-Ying (Université d'Ottawa / University of Ottawa, 2025)
Yanqing (erotic and love) literature has a long history in China and peaked during the mid-to late-Ming period (the mid 15th to 1644), paralleling the rise of luxury consumption and commerce. Many writers engaged in this genre, including a significant number of women. In an era dominated by traditional Confucian norms, it is notable how these female authors transcended social expectations to participate in literary pursuits, especially in yanqing literature, which was often considered outside the mainstream. More remarkably, women began forming literary communities centered on regional connections and establishing literary exchanges with male writers. This increased visibility allowed female writers to document their voices, marking a significant presence in Chinese literary history.
Keywords: Chinese History; Literary; Ming-Qing Dynasties; Women History